The Archaeology of Large-Scale Manipulation of Prey : The Economic and Social Dynamics of Mass Hunting - Bement, Leland C.; Carlson, Kristen, 1980- (Book collections on Project MUSE., 2018)
"Expands the understanding of large-scale hunting methods beyond the customary role of subsistence and survival to include the social and political realms where large-scale hunting adaptations evolved, primarily from the Americas and spanning from the Folsom Period on the Great Plains to the ethnographic present in Australia"--Provided by publisher